2005
DOI: 10.1002/dir.20034
|View full text |Cite
|
Sign up to set email alerts
|

Who are the multichannel shoppers and how do they perform?: Correlates of multichannel shopping behavior

Abstract: We develop a conceptual framework, which identifies the customer-level characteristics and supplier factors that are associated with purchase behavior across multiple channels. We also propose that multichannel shoppers provide benefits as measured by several customer-based metrics. We conduct an empirical analysis of our propositions using the customer database of a high technology hardware and software manufacturer. We find that customers who buy across multiple product categories, initiate more contacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
296
1
20

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(329 citation statements)
references
References 32 publications
12
296
1
20
Order By: Relevance
“…They prefer to use multiple channels when shopping, and multichannel consumers have specific characteristics that make them special: on average, they spend more money [42], buy more frequently [39], and have a longer customer lifetime value [64] than conventional shoppers. However, they are also more demanding and expect more from their shopping experiences [44].…”
Section: The Consumer's Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…They prefer to use multiple channels when shopping, and multichannel consumers have specific characteristics that make them special: on average, they spend more money [42], buy more frequently [39], and have a longer customer lifetime value [64] than conventional shoppers. However, they are also more demanding and expect more from their shopping experiences [44].…”
Section: The Consumer's Perspectivementioning
confidence: 99%
“…However, they are also more demanding and expect more from their shopping experiences [44]. Their shopping behavior is more exploratory, seeking more variety than consumers who buy in a single channel [39,56]. In addition, multichannel consumers consider their shopping experience holistically [31] and look for an integrated [77] and consistent experience between channels [58].…”
Section: The Consumer's Perspectivementioning
confidence: 99%
“…They have specific characteristics that make them special: on average, they spend more money (Venkatesan, V Kumar, & Ravishanker, 2007), buy more frequently (Kumar & Venkatesan, 2005), and have a longer customer lifetime value (Scott A. Neslin & Shankar, 2009) than conventional shoppers.…”
Section: Monográficomentioning
confidence: 99%
“…This approach is much like customercentric marketing function and includes various channels like internet, kiosks, call centres, direct marketing, catalogue, showrooms, etc. Many practitioners have reported that a customer using single-channel spends less in comparison to the customers using dual-channel or triple-channel (Kumar and Venkatesan, 2005;Myers et al, 2004). Thus, it is being stated that more channels bring more sales and profits for the companies (Neslin et al, 2006).…”
Section: Multichannel Approachmentioning
confidence: 99%